The Structure of the Seasonal Benthic Diatom Community and Its Relationship With Environmental Factors in the Yellow River Delta - Liu, Xing; Han, Jichang; Li, Yuhang; Zhu, Baohua; Li, Yun; Pan, Kehou (Frontiers in Marine Science, 2022)
Benthic diatoms are the main primary producers and are sensitive to environmental changes in the estuarine ecosystem. Therefore, it is critical to evaluate the impact of environmental stress on the benthic diatom community in the estuarine ecosystem. In this study, the sediment samples from the five sampling sites were collected from the Yellow River Delta in the four seasons, and the abundance of benthic diatom was determined using the high-throughput sequencing of 18S rRNA genes. The results showed that the motile-guild taxa, including Navicula, Nitzschia, and Amphora, dominated all communities throughout the sampling period. The structure of the benthic diatom community was significantly different among seasons (ANOSIM P < 0.01), especially between summer and winter. Redundancy analysis showed that water temperature and the concentrations of silicate, nitrate, ammonium, and pH value are the main driving factors shaping the seasonal assembly of the benthic diatom community. The results will improve knowledge about the benthic diatom community in the estuarine ecosystem and provide a theoretical foundation for estuary environmental management.